Indoor persistent organic pollutants in agricultural areas from Argentina - Tames, María Florencia (2020)
Persistent Organic Pollutants (POPs) are anthropogenic chemicals extensively used in the past forindustrial and agricultural purposes, characterized by their lipophilicity, ubiquity, volatility andenvironmental persistence. By other hand, chlorpyrifos is the most widely used current pesticide(CUPs) being the main insecticide used for crops in Argentina. The aim of this work was to assesslevels of POPs and CUPs in different fractions of airborne particles collected indoor in agriculturalareas from Argentina. Particles higher than 2.5 µm were trapped in polyurethane foams (PUF)while particles smaller than 1 µm and volatile compounds were adsorbed on activated charcoal.Compounds were analyzed by gas chromatograph with electron capture detector (GC-ECD).Endosulfans, chlordanes, PCBs, and HCHs were detected in all PUF samples, while endosulfans,chlorpyrifos, PCBs and HCHs were the most abundant in smaller particles. Majority of pesticidesshowed higher concentrations during the summer season (1397,7 vs 832,5 pg m-3). Even adding upall measured organic compounds no sample reach the threshold limit value for indoor pesticideslevels (0.1 pg m-3), neither in the large or small particle fraction. However, the fact that chronicexposure to POPs has been linked to several diseases, raises concern for human health.